ANTROPOLOGI EKONOMI : MASYARAKAT MEYBRAT DI KEPALA BURUNG PAPUA BARAT - Arius A. Kambu (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2014)
The purpose of this study is to explain in depth and thorough about the value of kinship and consumptive pattern that gives a clear impact on the pattern of the business establishment of Meybrat people. The sample access is all kinds of Meybrat people's business. This study used a qualitative analysis of a single case study approach. The results of this study found that (1) the business of Meybrat people is still at the stage of looking for shapes (innovation , triggering) where the personal character (personal values, education, experience, risk taking, internal control) are still weak in shaping the behavior of Meybrat people's business; (2) business groups (micro, small and medium enterprises) are more successful and grow well on an individual level than on groups; (3) Factors of kinship consumptive pattern systems and communities include: payment of dowry, families and relatives' education costs which is still a strong influence in shaping the conduct of business of Meybrat people. Keywords: Kinship, Consumer Pattern, Productive Economy